Does financial disadvantage at older ages eliminate the potential for better health?. Issue 10 (14th September 2007) - Montgomery, Scott M; Netuveli, Gopalakrishnan; Hildon, Zoe; Blane, David
Abstract : Objective: Taller adult stature reflects early life advantages and is an indicator of improved economic and health outcomes, and thus the potential for better health, including reduced depression risk. As inadequate retirement pension provision is an increasing concern, we investigated whether health potential (indicated by height) was realised among those experiencing financial disadvantage in later life. Design, setting and participants: Cross-sectional study of the population in England aged over 50 years and not resident in an institution. Participants (n = 9106) were members of the English Longitudinal Study of Ageing. Main outcome measure: Depression assessed using the eight-item Center for Epidemiological Studies Depression Scale. Results: Stratification by the lowest quintile of the net financial assets distribution defined adversity, and stature was dichotomised at the shortest quintile of height (sex standardised). After adjustment for sex, qualifications, occupation type, whether currently employed, age, ethnic origin and chronic illness, taller stature was associated with a statistically significant reduced risk of depression with an odds ratio of 0.7 (95% confidence interval 0.6 to 0.9) among those without financial disadvantage. No protection against depression was associated with taller stature among those with financial disadvantage (odds ratio 1.0; 95% confidence interval 0.8 to 1.3). Interaction testing confirmed effect modification by financial disadvantage for the association of height with depression (p = 0.005). Conclusions: Although taller stature, indicating favourable childhood conditions, is associated with a decreased risk of depression, this benefit is eliminated by financial disadvantage at older ages. Adequate financial provision for older people is required to maximise the health potential imparted by beneficial conditions in earlier life.